(untitled) (Critique Open Research & Review, 2023)
This research explores the development and optimization of Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) for enhancing the oral bioavailability of Furosemide, a widely used diuretic with poor aqueous solubility. The study focuses on the systematic formulation of Furosemide-loaded SNEDDS to overcome the challenges associated with its limited solubility, thereby improving its therapeutic efficacy. the SNEDDS formulations were meticulously designed using various excipients, including oils, surfactants, and co-surfactants, with the goal of achieving a stable and efficient nano emulsion. The selection of these components was based on their compatibility, emulsification capability, and ability to enhance drug solubility. The prepared formulations underwent a comprehensive optimization process employing experimental design methodologies to determine the optimal concentration of each component, ensuring the attainment of a balanced and stable SNEDDS. Physicochemical characterization of the optimized Furosemide SNEDDS was conducted to evaluate its particle size, zeta potential, polydispersity index, and drug-loading capacity. Additionally, the in vitro release profiles were assessed to understand the release kinetics of Furosemide from the SNEDDS. The optimized formulation exhibited favourable characteristics, including a small particle size, high drug-loading efficiency, and sustained drug release, suggesting its potential for improved oral bioavailability. Furthermore, the pharmacokinetic performance of the optimized Furosemide SNEDDS was investigated through in vivo studies, comparing it with conventional Furosemide formulations. The results demonstrated a significant enhancement in the bioavailability of Furosemide when delivered through the SNEDDS, attributed to the increased solubility and improved absorption of the drug. the formulated and optimized Furosemide SNEDDS presents a promising approach to address the solubility challenges associated with Furosemide, offering a potential solution to enhance its oral bioavailability. The study contributes valuable insights into the formulation design and optimization of SNEDDS for poorly water-soluble drugs, paving the way for improved therapeutic outcomes in the pharmaceutical field.